Epistemological Dynamics and Incorporation of Appraisal Practices in Kampala Archdiocesan Secondary Schools - Muweesi, Charles (Open Access Library Journal, 2018)
Using selected secondary schools in Kampala Archdiocese, the study was intended to establish the appraisal practices used to assess teachers’ performance in secondary schools in Kampala Archdiocese, Census and simple random sampling techniques were used to select the 196 respondents from a study sample population of 401 persons. Information was solicited through the use of face-to-face interviews with the head teachers and self-administered questionnaires which were distributed to teachers in the study area. Survey and questionnaire were used to collect data and after collecting data, descriptive statistics and percentages were computed with the help of SPSS computer package to analyze and facilitate discussion of findings. The study also found out that teachers are appraised; more than one performance appraisal method is used. It was concluded that among others, teachers’ negative attitude towards the performance appraisal process is one of the difficulties which beset its conduct. The study recommended that among others, management ought to ensure that there is effective communication and information dissemination to teachers immediately after the performance appraisal is conducted, the appraisers ought to adopt a more cooperative approach during the appraisal exercise, get the full participation of teachers and change their attitude towards the performance appraisal process, and sensitization should also be intensified on the relevance and purposes of performance appraisal on improving teachers’ performance. Subject Areas: Education Keywords: Appraisal Practices, Types of Appraisals, Ugandan Secondary Schools
Article